2012
DOI: 10.1042/bj20111817
|View full text |Cite
|
Sign up to set email alerts
|

Serum copper as a novel biomarker for resistance to thyroid hormone

Abstract: Thyroid hormone action is mediated by the thyroid hormone receptors TRα1 and TRβ. Defects in TRβ lead to RTH (resistance to thyroid hormone) β, a syndrome characterized by high levels of thyroid hormone and non-suppressed TSH (thyroid-stimulating hormone). However, a correct diagnosis of RTHβ patients is difficult as the clinical picture varies. A biochemical serum marker indicative of defects in TRβ signalling is needed and could simplify the diagnosis of RTHβ, in particular the differentiation to TSH-secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 38 publications
1
36
1
3
Order By: Relevance
“…Studies of Bastian et al (16,21,22) in mice showed that low levels of Cu were associated with a decreased TH state, which interfered with normal brain development. Similarly, serum ceruloplasmin and Cu levels have recently been proposed as direct biomarkers of TH signaling (54). In line with these studies, we observed strong positive associations between serum Cu and T 3 , rT 3 , and T 4 levels (Fig.…”
Section: Figuresupporting
confidence: 80%
“…Studies of Bastian et al (16,21,22) in mice showed that low levels of Cu were associated with a decreased TH state, which interfered with normal brain development. Similarly, serum ceruloplasmin and Cu levels have recently been proposed as direct biomarkers of TH signaling (54). In line with these studies, we observed strong positive associations between serum Cu and T 3 , rT 3 , and T 4 levels (Fig.…”
Section: Figuresupporting
confidence: 80%
“…Mittag et al [18, 24] have shown that hepatic trace element metabolism (e.g., Se) is modulated by T 3 . Thus, we aimed to test whether these effects might at least be partially mediated via TAMs by the administration of T 0 AM and 3-T 1 AM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other important related tests involving Cu metabolism (i.e., zinc, iron, selenium) and urine copper concentrations [3], were not reported and are often performed in cases of suspected copper metabolism disorders in humans [3,4]. In fact, the case study by Karaca and co-workers is more difficult to interpret than their conclusions might suggest.…”
mentioning
confidence: 96%